2016
DOI: 10.1515/rjim-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between the Autolytic Changes and Postmortem Interval in Refrigerated Cadavers

Abstract: Autolytic processes have a delayed onset and a much lower progression rate in a cold controlled environment. Different organs suffer different rates of autolysis in correlation to their structure and enzymatic content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 7 publications
4
25
2
3
Order By: Relevance
“…Similar to the 1911 study it was found that the connective tissue of organs broke down slower than the rest of the organ's cells 38 . In the liver it took up to 22 days for the full structure of the liver to be broken down, however by day 8 most of the blood vessels as well as hepatocytes began to lose their structure 38 . With the results from this study, the degradation of any DNA and liver cells prior to the placement of the livers in the growth chamber can be explained.…”
Section: Chapter 4: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Similar to the 1911 study it was found that the connective tissue of organs broke down slower than the rest of the organ's cells 38 . In the liver it took up to 22 days for the full structure of the liver to be broken down, however by day 8 most of the blood vessels as well as hepatocytes began to lose their structure 38 . With the results from this study, the degradation of any DNA and liver cells prior to the placement of the livers in the growth chamber can be explained.…”
Section: Chapter 4: Discussionsupporting
confidence: 76%
“…At temperatures just above freezing, autolysis still occurred within these organs, the liver included. While autolysis continued even at these cold temperatures, the rate was significantly lower than what was noted in 1911 38 . Similar to the 1911 study it was found that the connective tissue of organs broke down slower than the rest of the organ's cells 38 .…”
Section: Chapter 4: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…It is reported that in cases of autopsy lung autolytic changes are often observed which are also found in other types of tissues. Moreover, for some cases, histology is unremarkable [46,47], making the segmentation of lung autopsy histological slides is a challenging task due to the presence of autolytic changes of different grading causing indistinct tissue structure. Various morphological findings connected with age, coexistence of additional diseases, and hormonal stage of the patient are also significant and influence lung tissue.…”
Section: Datamentioning
confidence: 99%